55.9k views
19 votes
Desperate question down below

Desperate question down below-example-1

2 Answers

5 votes

Answer:

6

Explanation:


(2)/(3) (18 - 9)

Multiply
(2)/(3) with 18 and 9. Which would look like this:

(
(2)/(3) × 18 ) - (
(2)/(3) × 9 )

Calculate the values in the bracket and then subtract.

=
(36)/(3) -
(18)/(3)

=
(18)/(3)

= 6

User Adrianmanduc
by
5.7k points
10 votes

Answer:

6

Explanation:


(2)/(3) (18 - 9)

=
(2)/(3) × 9 ( cancel 3 and 9 by 3 )

= 2 × 3 = 6

User Julime
by
5.6k points